Investigation of the Surface Coating, Humidity Degradation, and Recovery of Perovskite Film Phase for Solar-Cell Applications - Amal Bouich; Julia Marí-Guaita; Faisal Baig; Yousaf Hameed Khattak; Bernabé Marí Soucase; Pablo Palacios (Nanomaterials, 2022)
Presently, we inquire about the organic/inorganic cation effect on different properties based on structure, morphology, and steadiness in preparing a one-step solution of APbI3 thin films, where A = MA, FA, Cs, using spin coating. This study was conducted to understand those properties well by incorporating device modeling using SCAPS-1D software and to upgrade their chemical composition. X-ray diffraction (XRD) was used to analyze the crystal structures. Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM) were conducted to characterize the surface morphology; photoluminescence, Transmission Electron Microscopy (TEM), and a UV–Visible spectrometer helped us to study the optical properties. The (110) plane is where we found the perovskite’s crystalline structure. According to the XRD results and by changing the type of cation, we influence stabilization and the growth of the <semantics>APbI3</semantics> absorber layer. Hither, a homogenous, smooth-surfaced, pinhole-free perovskite film and large grain size are results from the cesium cation. For the different cations, the band gap’s range, revealed by the optical analysis, is from 1.4 to 1.8 eV. Moreover, the stability of <semantics>CsPbI3</semantics> remains excellent for two weeks and in a ~60% humid environment. Based on the UV–Visible spectrometer and photoluminescence characterization, a numerical analysis for fabricated samples was also performed for stability analysis by modeling standard solar-cell structures <semantics>HTL/APbI3/ETL</semantics>. Modeling findings are in good agreement with experimental results that <semantics>CsPbI3</semantics> is more stable, showing a loss % in PCE of 14.28%, which is smaller in comparison to <semantics>FAPbI3</semantics> (44.46%) and <semantics>MAPbI3</semantics> (20.24%).